Aprendizagens em museu: uma análise a partir das experiências de crianças no museu Casa Kubitschek - Akemi Miqueline Takahashi (2021)
This dissertation had the following objectives: 1st) to evaluate the learning processes of children from the 3rd year of elementary school in a public school visiting the Casa Kubitschek Museum; and 2nd) from the analyzes carried out and the bibliography surveyed, create and produce artifacts aimed at raising the awareness of teachers of Basic Education for the relevance of museums as spaces for children's learning. To understand the meanings constructed by children in the context of the museum and in the classroom, before and after the visit, a qualitative study was carried out, with an emphasis on participant observation. The literature review and the selection of articles used in the theoretical framework was based on some assumptions, namely: 1st) education happens all the time and not only in the school context; and 2nd) the museum presents itself as an important space for learning. We dialogued with Jorge Larossa (2002) and the concept of experience; Paulo Freire (1987) and the defense of the protagonism of subjects; Latour (2002) on affective learning; Falk (2001) and free-choice learning. The data collection instruments were: observation; quiz; field notebook; record; and students' drawings. Each stage was described passing through moments in the school and in the museum, having been analyzed the conversation circles, the students' interactions, the speeches and the drawings that provided clues of how the children were affected and made the museum experience. The drawings could be interpreted as a form of communication and expression for children in the production of meanings and feelings. The results showed the possibility of free and sensitive learning present in the museum, in the interaction of children with human and non-human actants. The educational resources had the role of informing, disseminating and sensitizing Basic Education teachers about the multiple learning experiences in the museum, raising reflections on the subject-child-visiting-museum. Keywords: Experience. Sensitive learning. Affectation. Basic education